INTRODUCTION TRAVEL COMPANY PROFILE PT. TOUR SMAILING BASED Macromedia Flash MX - Tri Septina Wijayanti (Jurnal Sistem Informasi, 2005)
Introduction to company profiles with Macromedia Flash MX application is to facilitate consumers find products offered by PT. SMAILING TOUR, so that consumers can use the information in PT. SMAILING TOUR. With a system that can offer the information search easier both from within and outside the company.